Assessment of Competencies in Scientific Inquiry Through the Application of Rasch Measurement Techniques - Julia C. Arnold; William J. Boone; Kerstin Kremer; Jürgen Mayer (MDPI AG, 2018)
Achieving competence in scientific inquiry or mastering scientific practices is an essential element of scientific literacy. Clearly, if students’ Scientific Inquiry Competence (SIC) is to be improved, a critical step is to reliably measure it and provide from this measurement feedback for teaching. Although numerous instruments were presented in literature to assess SIC, the specific potential of Rasch measurement for the integration of research assessment and individual feedback onto SIC is so far underestimated. This article presents details regarding the design and evaluation of a test instrument using an open-response format to measure students’ SIC in content-rich biology contexts at the upper secondary level. First, a set of three sub-competences (“generating hypotheses„, “designing experiments„ and “analyzing data„) each composed of five competence aspects is introduced from literature to define the SIC construct. The SIC instrument was then operationalized using six open-ended partial-credit items. After pilot testing, the instrument was administered to N = 220 students (ages 15⁻19) before and after an inquiry-based unit on enzymes. Instrument functioning was evaluated using the Rasch Partial-Credit Model and first results towards satisfactory instrument functioning (e.g., validity and reliability) are presented. Particularly noteworthy is that the observed pattern in competence difficulty matched the pattern predicted from theoretical considerations. We demonstrate how the SIC instrument can be used for competence assessment and the evaluation of the effectiveness of learning.